Titanium dioxide nanoparticles decreases bioconcentration of azoxystrobin in zebrafish larvae leading to the alleviation of cardiotoxicity. (November 2022) - Nie, Hongyan; Pan, Meiqi; Chen, Juan; Yang, Qing; Hung, Tien-Chieh; Xing, Dan; Peng, Maomin; Peng, Xitian; Li, Guangyu; Yan, Wei
Abstract: Interactions between titanium dioxide nanoparticles (n-TiO2 ) and pollutants in the aquatic environment may alter the bioavailability of pollutants, and thus altering their toxicity and fate. In order to investigate the bioconcentration of azoxystrobin (AZ) and its mechanism of cardiotoxicity in the presence of n-TiO2, the experiment was divided into control, n-TiO2 (100 μg/L), AZ (40, 200 and 1000 μg/L) and AZ (40, 200, 1000 μg/L) + n-TiO2 groups, and the zebrafish embryos were exposed to the exposure solution until 72 h post-fertilization. Results suggested the presence of n-TiO2 notably reduced the accumulation of AZ in larvae compared with exposure to AZ alone, thereby significantly decreasing AZ-induced cardiotoxicity, including heart rate changes, pericardium edema, venous thrombosis, increased sinus venosus and bulbus arteriosus distance and changes in cardiac-related gene expression. Further studies showed that AZ + n-TiO2 together restrained total-ATPase and Ca 2+ -ATPase activities, while the activity of Na + K + -ATPase increased at first and then decreased. Furthermore, there were significant changes in the expressions of oxidative phosphorylation and calcium channel-related genes, suggesting mitochondrial dysfunction may be the potential mechanism of cardiotoxicity induced by AZ and n-TiO2 . This study supplies a new perspective for the joint action of AZ and environmental coexisting pollutants and provides a basis for ecological risk management of pesticides. Graphical abstract: Image 1 Highlights: Co-exposure with n-TiO2 decreased AZ bioconcentration in zebrafish embryos. AZ induced cardiotoxicity in zebrafish embryos. AZ interfered with mitochondrial function and calcium channels. The presence of n-TiO2 alleviated AZ-induced cardiotoxicity.